Extended generalized Riccati equation mapping method for the fifth-order Sawada-Kotera equation - Naher, Hasibun; Abdullah, Farah Aini; Mohyud-Din, Syed Tauseef (© 2013 AIP Advances, 2016)
This article was published in the AIP Advances [© 1998 ] and the definite version is available at : http://dx.doi.org/10.1063/1.4804433 The Journal's website is at: http://scitation.aip.org/content/aip/journal/adva/3/5/10.1063/1.4804433